Peningkatan kompetensi guru penggerak melalui kegiatan loka karya di BBGP Jatim: Balai Besar Guru Penggerak Jawa Timur - M Saleh, Mufliha Rahma (Maliki Interdisciplinary Journal, 2024)
The study looked at how effective the 5th PGP Workshop of the 9th Army held by the Great Hall of Engineers (BBGP) of East Java Province was in improving the ability of future engineers. This study analyzes various aspects of the workshop activity. This includes follow-up evaluation, determination of actors, program planning, and data mining. The results showed that the workshop was successful in providing participants with practical knowledge and useful experience to build and implement effective educational programmes. The program continues to succeed thanks to support from all sides, troubleshooting strategies, and commitment to improvement. In the long run, this research is expected to enhance the ability of mobilizing teachers to lead change in their respective schools. This will enable an improvement in the quality of education in the region as a whole.